2018
DOI: 10.1002/jms.4062
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cu+ and Cu2+ with peptides: Peptides = oxytocin, Arg8‐vasopressin, bradykinin, angiotensin‐I, substance‐P, somatostatin, and neurotensin

Abstract: The intrinsic binding ability of 7 natural peptides (oxytocin, arg -vasopressin, bradykinin, angiotensin-I, substance-P, somatostatin, and neurotensin) with copper in 2 different oxidation states (Cu ) derived from different Cu precursor sources have been investigated for their charge-dependent binding characteristics. The peptide-Cu complexes, [M - (n-1)H + nCu ] and [M - (2n-1)H + nCu ], are prepared/generated by the reaction of peptides with CuI solution/Cu-target and CuSO solution and are analyzed by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
(170 reference statements)
2
4
0
Order By: Relevance
“…Notably, more hindered thiols such as t -BuSCH 2 SH and EtSCHMeSH showed reduced activity toward MOR244-3 in the presence of copper. Both Cu­(I) and Cu­(II) species should be available to ORs given the known reducing environment within cells and the demonstrated binding ability of both Cu­(I) and Cu­(II) with peptides …”
Section: Deorphaned Ors Exemplifiedsupporting
confidence: 86%
See 1 more Smart Citation
“…Notably, more hindered thiols such as t -BuSCH 2 SH and EtSCHMeSH showed reduced activity toward MOR244-3 in the presence of copper. Both Cu­(I) and Cu­(II) species should be available to ORs given the known reducing environment within cells and the demonstrated binding ability of both Cu­(I) and Cu­(II) with peptides …”
Section: Deorphaned Ors Exemplifiedsupporting
confidence: 86%
“…Both Cu(I) and Cu(II) species should be available to ORs given the known reducing environment within cells and the demonstrated binding ability of both Cu(I) and Cu(II) with peptides. 120 Because cysteine, histidine, and methionine frequently coordinate copper in cuproenzymes, site-directed mutagenesis experiments were performed with MOR244-3, mutating these three amino acids. Complete loss of response to MTMT was observed in some cases, while response to nonsulfurous ligands was maintained, suggesting that only copper/ligand binding was disrupted.…”
Section: Deorphaned Ors Exemplifiedsupporting
confidence: 77%
“…For example, Cu 2−x S is very different from Cu 2−x O but shows a similar structure to Cu 2−x Se (klockmannite) [9]. CuS compound is paramagnetic due to the 3d 9 electron arrangement, and some studies have reported that all Cu atoms in CuS have an oxidation state of Cu + based on XPS results [10]. However, it can be attributed to (Cu + ) 2 Cu 2+ S 2 with both Cu(I) and Cu(II) in the XRD crystal structure results [11].…”
Section: Introductionmentioning
confidence: 99%
“…Met-11, Leu-10 and Lys-3 were found on the anchoring sites for Cu(II) in SP, according to calculated binding energies determined by DFT. Noteworthily, the pH of the studied solutions was in the range of 2 to 3 [ 145 ]. It was also suggested that SP is not able to bind Cu(II) ions selectively in a solution environment at a physiological pH.…”
Section: Tachykinins Complexes With Trace Elementsmentioning
confidence: 99%